2018
DOI: 10.1111/dme.13857
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of gestational diabetes mellitus: a nationwide multicentre prospective study

Abstract: Aim Prevalence rates of gestational diabetes mellitus (GDM) show considerable variation among different countries and regions of the world. The primary aim of this study was to determine the nationwide prevalence and predictors of GDM in Turkey. Methods We conducted prospective nationwide screening among pregnant women. Between August 2016 and November 2017, a total of 2643 pregnant women from 51 centres in 12 different regions were enrolled. A two‐step screening method and Carpenter and Coustan criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
3
22
2
1
Order By: Relevance
“…Up to 6-7% of pregnancies are thought to be complicated by diabetes mellitus and approximately 86% of these cases are gestational diabetes mellitus (12). In a large-sized study from Turkey, the authors stated that the national prevalence of GDM was found to be 16.2% without a significant difference between urban and rural regions (13). In another cross-sec-…”
Section: Gynecol Obstet Reprod Med 2019;25(1)22-27mentioning
confidence: 97%
“…Up to 6-7% of pregnancies are thought to be complicated by diabetes mellitus and approximately 86% of these cases are gestational diabetes mellitus (12). In a large-sized study from Turkey, the authors stated that the national prevalence of GDM was found to be 16.2% without a significant difference between urban and rural regions (13). In another cross-sec-…”
Section: Gynecol Obstet Reprod Med 2019;25(1)22-27mentioning
confidence: 97%
“…A recent study on worldwide GDM prevalance revealed that Middle East and North Africa has the highest prevalance with a median estimate of 12.9% (range 8.4%–24.5%) whereas Europe with a median estimate of 5.8% (range 1.8%–22.3%) has the lowest prevalance 2 . According to a study from Turkey where the present study conducted in, nation‐wide prevalance of GDM was found to be 16.2% 3 . Another study from Turkey reported a prevalance of 6.07% 4 .…”
Section: Introductionmentioning
confidence: 46%
“…Thirty healthy and 30 patients who met criteria for GDM were included in this study. Questionnaire details and subsequent screening strategy for GDM, including a sample flowchart of our study, were present in a nationwide multicenter prospective study [20]. The exclusion criteria used in this study were based on the guidelines of IADPSG (2015 version) with some modifications [21,22].…”
Section: Methodsmentioning
confidence: 99%